Pengaruh Arus Listrik Spot Welding KW14-1031 Terhadap Kekuatan Geser Pada Baja St42 - I Wayan Suma Wibawa; I Made Anom Adiaksa; Made Ardikosa Satrya Wibawa; A.A. Gede Pradnyana Diputra; I Komang Kantun; I Nyoman Suparta (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Welding technology serves not only as a manufacturing process but also as a repair solution for all metal-based components. Spot welding is a welding method that utilizes electrical resistance to join various products made of sheet metal, in which the contacting metal surfaces are fused by the heat generated from electrical resistance. This welding method is selected due to several advantages, including ease of operation without requiring specialized skills as demanded by other welding techniques, as well as a faster process that enhances production time efficiency. Control of the electrical current path during welding is critical, as it significantly influences the characteristics of the joint, including weld quality, shear strength, hardness level, and resistance to external loads. This study focuses on analyzing the effect of electrical current in spot welding techniques on the shear strength of ST 42 steel plates. Through descriptive analysis and graphical representation, this research aims to observe the relationship between electrical current and the resulting shear strength produced by the welding process. The lowest average shear strength was recorded at an input current of 20.36 A with a welding output current of 6011.47 A, a welding time of 8 seconds, and a heat input of 61894.30 J, yielding a shear strength of 1.67 MPa. Meanwhile, the highest average shear strength was obtained at an input current of 28.95 A with a welding output current of 6011.47 A, a welding time of 8 seconds, and a heat input of 88007.92 J, resulting in a shear strength of 6.72 MPa. Electrical current control is therefore essential, as ST 42 steel plates experienced damage at an input current of 32.45 A and an output current of 6323.58 A, with a welding time of 8 seconds and a heat input of 98647.84 J.